Review on crosstalk and common mechanisms of endocrine disruptors: Scaffolding to improve PBPK/PD model of EDC mixture. (February 2017) - Sharma, Raju Prasad; Schuhmacher, Marta; Kumar, Vikas
Abstract: Endocrine disruptor compounds (EDCs) are environment chemicals that cause harmful effects through multiple mechanisms, interfering with hormone system resulting in alteration of homeostasis, reproduction and developmental effect. Many of these EDCs have concurrent exposure with crosstalk and common mechanisms which may lead to dynamic interactions. To carry out risk assessment of EDCs' mixture, it is important to know the detailed toxic pathway, crosstalk of receptor and other factors like critical window of exposure. In this review, we summarize the major mechanism of actions of EDCs with the different/same target organs interfering with the same/different class of hormone by altering their synthesis, metabolism, binding and cellular action. To show the impact of EDCs on life stage development, a case study on female fertility affecting germ cell is illustrated. Based on this summarized discussion, major groups of EDCs are classified based on their target organ, mode of action and potential risk. Finally, a conceptual model of pharmacodynamic interaction is proposed to integrate the crosstalk and common mechanisms that modulate estrogen into the predictive mixture dosimetry model with dynamic interaction of mixture. This review will provide new insight for EDCs' risk assessment and can be used to develop next generation PBPK/PD models for EDCs' mixture analysis. Highlights: EDCs' mechanism involves multiple targets interfering hormone synthesis, metabolism and their biological action. Toxicodynamic interactions like crosstalk and common mechanisms are very important for elucidating the mixture effect. Window of exposure plays an important role in assessing the risk for developmental and reproductive disorders. In silico risk prediction can be improved by integrating toxicodynamic interactions of EDCs.